Managing public road transportation for sustainable and safety during implementation: An empirical study - Giri, Om Prakash; Lamichhane, Basu Dev; Adhikari, Ritu; Koirala, Madhav Prasad (Edelweiss Applied Science and Technology, 2025)
This study investigates the sustainability of public road construction management in Nepal, emphasizing socioeconomic and environmental factors, as well as opportunities and challenges during the construction phase of highway expansion projects, focusing on the Damauli section of the Mugling–Pokhara road. Primary data were collected through field observations and questionnaire surveys involving consultants, contractors, and local residents (85 respondents). Secondary data were sourced from reports, articles, and online platforms. Descriptive statistics using MS Excel and SPSS were applied to present data through tables and bar charts. The construction phase caused significant disruptions, including traffic congestion, dust, noise, and air pollution, affecting daily life. However, it also created local business and employment opportunities. A newly constructed side lane helped alleviate some negative impacts, illustrating both the challenges and benefits of highway construction. While construction activities pose temporary hardships to communities, they also offer socioeconomic opportunities. Balancing these effects is vital for achieving sustainable road development. The study offers valuable insights for policymakers, planners, regulators, and investors in understanding the dual impacts of road construction and planning more sustainable infrastructure projects that maximize benefits while minimizing disruptions.